PSYCHOLOGICAL CHARACTERISTICS OF THE MANIFESTATION OF ADOLESCENT EMPATHY (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, the psychological aspects of the manifestation of empathy in adolescents, the content of the concept of empathy and its psychological characteristics, theoretical and practical ideas are put forward.